Ecological characteristics of subterranean termites in Mamar agroforestry, West Amarasi, Timor Island, Indonesia - DINA TIARA KUSUMAWARDHANI; ORIGENES BOY KAPITAN; MITHA RABIYATUL NUFUS (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kusumawardhani DT, Kapitan OB, Nufus MR. 2025. Ecological characteristics of subterranean termites in Mamar agroforestry, West Amarasi, Timor Island, Indonesia. Biodiversitas 26: 5857-5869. Mamar, a traditional agroforestry system on Timor Island, Indonesia, is overgrown with various local and introduced forest trees, and fodder crops, which influence the organic matter that needs to be decomposed. Subterranean termites act as decomposers, although the specific species remains unidentified. This study, conducted in Soba Village, West Amarasi Sub-district, Kupang District, East Nusa Tenggara, Indonesia, aimed to identify termite species in Mamar, analyze their environmental conditions, and assess the soil characteristics within and around their nests. The study utilized a 150x250 m sample plot across three locations, each representing different contours, altitudes, and soil colors of Mamar. Two successfully identified species of subterranean termites from eight nest, Macrotermes gilvus NC034110.1 and Nasutitermes matangensis MTR C-004. Environmental parameters (temperature, humidity, and light intensity) were monitored over three months (March-July) showing ranges of 23.03-28.65°C, 65.41-84.87%, and 594.19-2529.9 lux, respectively. These conditions were generally suitable for termite activity, although humidity levels occasionally dropped below optimal. Soil characteristics focused on moisture content, soil acidity (pH value), C-organic, total nitrogen, organic matter, and texture of the three fractions. Nest soils exhibited higher pH, carbon, nitrogen, and organic content compared to surrounding soils. Moisture content varied by texture, higher in clay, lower in loam and clay loam. As decomposers and soil engineers, both termites can contribute to improving the inceptisol soil properties of Mamar by enriching organic matter. The greater the number of plants in Mamar, the more it influences termite activity, especially M. gilvus, which needs raw materials to make fungus comb in their nests. Meanwhile, the island’s dry climate and low rainfall force termites to adapt to suboptimal moisture conditions, even within their own nests.